Academic Libraries' Outreach Efforts: Identifying Themes in the Literature. Issue 3 (3rd July 2019) - Blummer, Barbara; Kenton, Jeffrey M.
Abstract : Outreach programs remain essential in fostering the use of library collections and services. A review of one hundred seventy-four papers on academic library outreach from 2008 to January 2019 highlighted the popularity of these programs during this period as well as the identification of five themes. These themes point to the importance of library outreach to targeted groups, the popularity of specialized library outreach programs, the need for collaboration in fostering outreach efforts, the benefits of managing these programs and the use of social media for library outreach. Foremost, these materials highlight opportunities and challenges for librarians in providing library outreach in academic institutions.